Deficyty gotowości szkolnej przedszkolaka – można im łatwo zapobiec. Od zintegrowanej diagnozy do skutecznego wspierania rozwoju dziecka - Suchodolska, Jolanta (Studia Edukacyjne, 2020)
The levels of skills, abilities and adaptability achieved by a child within a kindergarten community becomes a natural entry pass to participate in a wider peer community which is formed by children taking up the challenge of school education. The differences between children starting school education are visible in the fieldof broadly construed self-reliance (spatial, manual, self-service, task-based) and in numerous abilities to react, communicate and learn, gained and improved within the first6 years of life. They can result from the multiple factors connected with the child’s diversifiedpotential, the degree to which the child’s social and educational needs are taken care of. Furthermore, there are exogenous factors involved which affect the pace and character of the development process in an unusually individualized way, which in turn heavily depends on the specificsituation and the upbrin-ging methods applied. All of the above result in a situation where the differences in an individual’s readiness for school become a crucial parametric indicator which, when disregarded, can expose the child to failures during his attempts to adapt to a new environment until optimal conditions are created to enable the child to achieve success.This study provides the proposals to be used while trying to provide support for the child’s individual development and aims at protecting the child from failures at the beginning of school education or eliminating the risk of exclusion connected with the existing failures.